2014
DOI: 10.1177/1045389x14523854
|View full text |Cite
|
Sign up to set email alerts
|

Optimum resistive loads for vibration-based electromagnetic energy harvesters with a stiffening nonlinearity

Abstract: The exploitation of nonlinear behavior in vibration-based energy harvesters has received much attention over the last decade. One key motivation is that the presence of nonlinearities can potentially increase the bandwidth over which the excitation is amplified and therefore the efficiency of the device. In the literature, references to resonating energy harvesters featuring nonlinear oscillators are common. In the majority of the reported studies, the harvester powers purely resistive loads. Given the complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…The analysis of the energy harvester often involves determining the power transferred to the electrical load and the optimal load condition. Due to the complexity of nonlinear behaviours, the analysis can be achieved with the following simplifications [36,37]:…”
Section: Magnetically Levitated Harvestermentioning
confidence: 99%
“…The analysis of the energy harvester often involves determining the power transferred to the electrical load and the optimal load condition. Due to the complexity of nonlinear behaviours, the analysis can be achieved with the following simplifications [36,37]:…”
Section: Magnetically Levitated Harvestermentioning
confidence: 99%
“…The work presented here builds on the findings of [19]. In [19] it has been demonstrated that under optimal conditions a nonlinear energy harvester can deliver as much power as a linear harvester to a purely resistive load.…”
Section: Introductionmentioning
confidence: 98%
“…In [19] it has been demonstrated that under optimal conditions a nonlinear energy harvester can deliver as much power as a linear harvester to a purely resistive load. For this to be achieved both the resistive load and the underlying linear frequency ω n must be selected carefully.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations